2001
DOI: 10.1097/00000658-200102000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Maneuvers Enhance Molecular Detection of Circulating Tumor Cells During Gastric Cancer Surgery

Abstract: ObjectiveTo evaluate the relation between the presence of cancer cells in blood according to the time course during a surgical procedure and liver metastases in patients with gastric cancer. Summary Background DataSeveral studies have reported on the detection of circulating cancer cells in blood by reverse transcriptase-polymerase chain reaction (RT-PCR). However, few reports have examined the relation between molecular detection of circulating cancer cells according to the time course during a surgical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 18 publications
3
61
0
Order By: Relevance
“…(14)(15)(16)(17)(18) We reported that the presence of CTC correlates with tumor progression and outcomes of patients with esophageal, gastric and biliary-pancreatic cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(14)(15)(16)(17)(18) We reported that the presence of CTC correlates with tumor progression and outcomes of patients with esophageal, gastric and biliary-pancreatic cancer.…”
mentioning
confidence: 99%
“…(12,13) The RT-PCR is a useful assay for detecting circulating tumor cells (CTC) within blood specimens from patients with various malignancies, including gastric cancer. (14)(15)(16)(17)(18) We reported that the presence of CTC correlates with tumor progression and outcomes of patients with esophageal, gastric and biliary-pancreatic cancer.(14-18) Several epithelial-specific antigens such as CEA, cytokeratin-19, and cytokeratin-20, have been used generally in many studies of CTC detection in gastric cancer. (15,19) However, recent studies have found false-positive results in RT-PCR assays using these markers for CTC detection.…”
mentioning
confidence: 99%
“…16‐34 The gap observed in the incidence of CTC among each study may be as a result of differences in the clinicopathological backgrounds of enrolled patients, target markers, blood volumes assessed by PCR, and the cut‐off values for mRNA levels. However, the incidence of CTC ranged between 36.6% and 52.2% in five RT‐PCR studies targeting CEA, which is one of the conventional PCR markers for the detection of CTC 17, 18, 19, 21, 29. According to studies assessed in this review article, positive rates of serum CEA ranged between 24.3% and 26.3% 21, 29, 31.…”
Section: Incidence Of Ctcmentioning
confidence: 89%
“…reported that the positive rates for CEA mRNA expression before and after gastrectomy were 8.8% (5/57) and 33.3% (19/57), respectively 17. Moreover, they demonstrated a close relationship between the presence or absence of CEA mRNA expression and disease recurrence, such as liver metastases 17. The findings of this study suggest that surgical maneuvers enhance the metastatic process from the detachment of primary tumor cells into the systemic circulation in patients with gastric cancer.…”
Section: Incidence Of Ctcmentioning
confidence: 99%
“…Concomitant molecular analysis for CTCs with a multimarker panel is justifiable supplementary approaches to current pathological staging system, which may help physicians make accurate judgment on clinical treatments and predicting prognosis for GC patients. The high false positive rate (43.5%) of membrane array in the prediction of postoperative recurrence/metastasis, at least in part, might result from the timing of blood sampling during surgical procedures, 37 which probably enhanced the relief of CTCs. A blood sampling procedure carried out before or after operation can be a resolution to overcome such a problem.…”
Section: Discussionmentioning
confidence: 99%